2009
DOI: 10.1111/j.1365-2222.2009.03260.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjuvant and adjuvant‐free murine experimental asthma models

Abstract: IntroductionThe most widely used protocol for the induction of experimental allergic airway inflammation in mice involves sensitization by intraperitoneal (i.p.) injections of the antigen ovalbumin (OVA) used in conjunction with the adjuvant aluminium hydroxide (alum). Although adjuvants are frequently used, there are questions regarding the necessity of alum for murine asthma studies due to the non-physiological nature of this chemical.ObjectiveThe objective of this study was to compare experimental asthma ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 42 publications
7
86
1
7
Order By: Relevance
“…Examination of the differential cell types showed a specific reduction in the number of eosinophils ( fig. 2b), which are the predominant inflammatory cell infiltrate in this model [23]. In contrast, the moderate increase seen in the numbers of lymphocytes and neutrophils in the BALF following allergen challenges was not affected by NA treatment ( fig.…”
Section: Clara Cell Depletion Suppresses Allergic Lung Inflammationmentioning
confidence: 73%
See 2 more Smart Citations
“…Examination of the differential cell types showed a specific reduction in the number of eosinophils ( fig. 2b), which are the predominant inflammatory cell infiltrate in this model [23]. In contrast, the moderate increase seen in the numbers of lymphocytes and neutrophils in the BALF following allergen challenges was not affected by NA treatment ( fig.…”
Section: Clara Cell Depletion Suppresses Allergic Lung Inflammationmentioning
confidence: 73%
“…Assessment of leukocyte distribution in bronchoalveolar lavage fluid 48 h after the last challenge, mice were sacrificed and bronchoalveolar lavage fluid (BALF) was generated as described previously [23]. The total number of leukocytes was determined using a Casy TT Cell Counter (Schärfe System GmbH, Reutlingen, Germany).…”
Section: Airway Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…(15,16) In addition, alum has been shown to cause major stress in animals up to 4 h after exposure. (6) Studies in which alum was not used demonstrated that this substance is not necessary for the induction of an allergic response in the lungs of mice and that there is no difference between subcutaneous sensitization without the use of adjuvants and intraperitoneal sensitization with alum. Those studies, involving protocols without the use of adjuvants, demonstrated different levels of in BAL fluid or in terms of EPO levels in lung tissue.…”
Section: Resultsmentioning
confidence: 99%
“…(6,7) The results of that study allow the exclusion of the use of adjuvants in murine models of asthma in future studies; the artificial way in which asthma is currently studied in animal models, with the use of adjuvants, has been justifiably criticized. However, in that study, there were three sensitizations, 7 disposed of in accordance with the norms of the institution.…”
Section: Introductionmentioning
confidence: 99%